Meghdoot mobile app: Upgrades in 2023 - Dhulipala, Ram; Singh, Kanika (ILRI, 2023)
The Meghdoot mobile app was developed in the year 2020 to provide location and crop specific weather-based agro-advisories across India. The app was refined after receiving suggestions and feedback from various experts in the field. Meghdoot presents observed and forecast information on temperature, rainfall, wind direction and humidity downscaled to a specific location along with an agromet advisory generated and managed by the India Meteorological Department (IMD) and Indian Institute of Tropical Meteorology (IITM). The design and architecture of Meghdoot benefited from the reference architecture of two previous applications developed by ICRISAT with support from CCAFS: The Sowing App and the Intelligent Agricultural Systems Advisory Tool (iSAT). Both these applications demonstrated the effective use of software to support generation of agrometeorological advisories. The DI team at ILRI is building off from the collaborations and outputs from erstwhile CCAFS and continuing to co-design improvements to Meghdoot as well as the backend platform with IMD and IITM.